Ictal SPECT in Sturge-Weber syndrome - Bilgin, O (2008)
We report on a patient with right-sided Sturge-Weber syndrome (SWS), in whom earlier functional hemispherectomy failed. Subtraction of ictal and interictal single-photon-emission-computed-tomography (SPECT) superimposed on individual MRI showed a right fronto-orbital hyperperfusion, with a left-sided EEG seizure pattern. Ictal SPECT supported our assumption that right frontal originated seizure pattern propagated to left hemisphere via the remaining right frontal bridge. Right orbito-frontal resection and disconnection from corpus callosum resulted in seizure freedom.